Morphological, hematological, biochemical characteristics, and food preferences of common teal (Anas crecca) during the wintering period in Punjab, Pakistan (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The study aims to investigate sexual dimorphism in common teal (Anas crecca) by comparing various morphological, hematological, and biochemical parameters between males and females. Materials and Methods: 27 freshly captured wintering teals were collected from hunters holding valid shooting licenses and were subjected to hematological, biochemical, and food preference analysis following all relevant ethical guidelines for animal research. Results: Several morphological traits showed significant sexual dimorphism, including body length, wingspan, primary wing length, tail length, beak length, and head length, while body weight, tarsal and metatarsal lengths, and body circumference showed no significant differences. Hematological parameters such as red blood cells count, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and red cell distribution width-standard deviation differed significantly between sexes. Biochemical analysis revealed notable differences in urea, protein, and albumin levels. No significant difference in dietary preferences was observed between males and females. Conclusion: Morphological differences between males and females were observed except for parameters such as body weight, tarsal length, metatarsal length, and body circumference. Dietary preference was non-significant between genders. These findings would contribute to a deeper understanding of sexual dimorphism in common teal and may inform future research on migratory behavior, habitat use, and conservation strategies tailored to sex-specific ecological needs.J. Adv. Vet. Anim. Res., 12(4): 1132–1141, December 2025http://doi.org/10.5455/javar.2025.l974